A novel monostable multivibrator circuit - Tuwanut, Panwit; Koseeyaporn, Jeerasuda; Wardkein, Paramote (My University, 2005)
This article represents a novel monostable multivibrator circuit in which width and height of the pulse output can be independent electronically adjusted. In addition, the pulse width of output is not restricted to be wider or narrower than that of input pulse as conventionally employed. Namely, there is no restriction on the width of input and output pulse, the circuit's implementation is thus more convenient. The proposed circuit is composed of three OTAs, two resistors and one capacitor, basically constructed a simple pulse generator (Schmitt-trigger circuit). Therewith the compactness of the circuit, It Is thus suitable to be fabricated for integrated circuit. The results of circuit simulation is accordance well with theoretical analysis.
Keywords: Analog circuit; Monostable multivibrator; PPM; PWM